1980
DOI: 10.1002/1097-0142(19800101)45:1<191::aid-cncr2820450130>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Parity and prognosis in breast cancer

Abstract: Analysis of five-year disease-free survival rates in 608 women with operable breast cancer revealed that the reproductive history is a significant prognostic determinant. Overall parous women had a significantly higher cumulative five-year disease-free survival rate (60%), compared to the nulliparous (46%) (z = 2.5, p = 0.012). Significant differences were also noted when gravidity in addition to parity was taken as the determinant. The corresponding disease-free survival rates were 61% and 50%, respectively (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…When all histologies were combined, there was a decreased risk of breast cancer-specific mortality similar in magnitude to previous studies [20,4]. Anderson et al [4] found an increased 10-year survival rate in their participants who had ever experienced childbirth compared to nulliparous women (92% survival vs. 76%; P =0.002).…”
Section: Discussionsupporting
confidence: 74%
“…When all histologies were combined, there was a decreased risk of breast cancer-specific mortality similar in magnitude to previous studies [20,4]. Anderson et al [4] found an increased 10-year survival rate in their participants who had ever experienced childbirth compared to nulliparous women (92% survival vs. 76%; P =0.002).…”
Section: Discussionsupporting
confidence: 74%
“…This finding is puzzling since the effect is directly opposite to the protective influence of early delivery on breast cancer incidence (Kelsey & Hildreth, 1983). Morrison et al (1972), did not find any relationship between age at delivery and survival and the results of other, smaller studies of parity and prognosis have produced conflicting results (Papatestas et al, 1980;Black et al, 1983). Contrary to the suggestion of Daniel (1980) cigarette use was not related to prognosis in our patients.…”
Section: Discussionmentioning
confidence: 92%
“…However, several early studies suggested that factors influencing cancer incidence might also affect subsequent survival (6)(7)(8). With breast cancer, for example, higher total energy and polyunsaturated fat intakes, risk factors of mammary tumors, are also associated with a poor prognosis (6); nulliparous women, at elevated risk of breast cancer, also have a significantly lowered cumulative five-year diseasefree survival rate compared with parous individuals (7). In terms of gastric cancer, Fontana's study suggested that low socioeconomic status was a poor prognostic factor and was also associated with a high risk (8).…”
Section: Introductionmentioning
confidence: 99%